Design an Application Programming Interface for a Population Social Welfare Survey Application in the Context of System Integration - Moh Anshori Aris Widya; Lia Meta Sari (NEWTON: Networking and Information Technology, 2021)
In order to realize the population welfare program, the Sumbermulyo village government, Jogoroto District, Jombang Regency, East Java Province made efforts to overcome various poverty cases that occurred in the Sumbermulyo village community. One of them is applying for DKTS (Social Welfare Integrated Data) assistance for the poor to the Social Service. The amount of wealth owned is a benchmark in determining whether to receive government assistance. People who are at a minimum level of wealth will be included in the category of underprivileged people and can apply for DKTS to the local government. The DKTS submission process is carried out starting from collecting data on the poor by the survey officer then the survey officer comes to the poor community to validate the data using the android application. The system development is built with integrated website and android technology to facilitate data processing. The system integration process uses an Application Programming Interface (API) that connects applications with one another across platforms. The application of the API will make it easier for the system to access data so that it does not take long to obtain data information.